RNA transcript sequencing reveals inorganic sulfur compound oxidation pathways in the acidophile Acidithiobacillus ferrivorans - Christel, S.; Fridlund, J.; Buetti-Dinh, A.; Buck, M.; Watkin, Elizabeth; Dopson, M. (2016)
Acidithiobacillus ferrivorans is an acidophile implicated in low-temperature biomining for the recovery of metals from sulfide minerals. Acidithiobacillus ferrivorans obtains its energy from the oxidation of inorganic sulfur compounds, and genes encoding several alternative pathways have been identified. Next-generation sequencing of At. ferrivorans RNA transcripts identified the genes coding for metabolic and electron transport proteins for energy conservation from tetrathionate as electron donor. RNA transcripts suggested that tetrathionate was hydrolyzed by the tetH1 gene product to form thiosulfate, elemental sulfur and sulfate. Despite two of the genes being truncated, RNA transcripts for the SoxXYZAB complex had higher levels than for thiosulfate quinone oxidoreductase (doxDA genes). However, a lack of heme-binding sites in soxX suggested that DoxDA was responsible for thiosulfate metabolism. Higher RNA transcript counts also suggested that elemental sulfur was metabolized by heterodisulfide reductase (hdr genes) rather than sulfur oxygenase reductase (sor). The sulfite produced as a product of heterodisulfide reductase was suggested to be oxidized by a pathway involving the sat gene product or abiotically react with elemental sulfur to form thiosulfate. Finally, several electron transport complexes were involved in energy conservation. This study has elucidated the previously unknown At. ferrivorans tetrathionate metabolic pathway that is important in biomining.